METAFORA PADA LIRIK LAGU DALAM ALBUM UNTUK DUNIA, CINTA DAN KOTORNYA KARYA NADIN AMIZAH - Triani, Iin; Sulissusiawan, Ahadi; Muzammil, Ahmad Rabiul (Universitas Tanjungpura, 2025)
In general, the purpose of this research is to gain a deeper understanding of the use of metaphor in the song lyrics of the album Untuk Dunia, Cinta, dan Kotornya by Nadin Amizah, and to reveal important aspects of literary style that can enrich public knowledge, particularly in the field of stylistics and the study of song lyrics as literary works. This research uses a descriptive method with a qualitative approach, and the data is obtained through document study and non-participant observation techniques. The data analysis is carried out qualitatively, using Ullman’s theory of metaphor as the analytical framework. This research identifies three types of metaphors used in the lyrics: anthropomorphic metaphors 13 instances, metaphors from concrete to abstract 16 instances, and synesthetic metaphors 10 instances. No animal metaphors were found in the analyzed data. Based on the findings, it is evident that metaphor from concrete to abstract is the most dominant, followed by anthropomorphic and synesthetic metaphors. These results show that Nadin Amizah’s lyrical writing style is rich in abstract, emotional, and subjective elements, which reflect the unique characteristics of her musical works. It is hoped that this study can serve as a reference for further research in stylistic analysis and lyric-based literary studies.